(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract The current research sought to demonstrate the effect of material flow cost accounting on reducing products through the application of material flow cost accounting technique, which works on the optimal utilization of materials and energy and the reduction of environmental impacts.The research aims to clarify the knowledge foundations for material flow cost accounting, in addition to studying the material flow cost accounting technique that helps reduce the cost of products and make them environmentally friendly. To achieve this, the research relied on the descriptive approach with regard to the theoretical aspect of the research, by relying on Arab and foreign books, letters, dissertations, and articles related to the subject of the research. And personal interviews with workers and engineers. The research reached a set of conclusions, the most important of which is that accounting for material flow costs contributes to reducing costs and determining environmental costs represented by waste and emissions generated from the production process. In addition, material flow cost accounting allows a complete picture of the use of materials and energy that enters the production path (whether it is included in the composition of the final product and by-products first). The research came out with a set of recommendations, the most important of which is the need to use material flow cost accounting for the purpose of determining the cost of products.